(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2021)
This was a qualitative study of learners with epilepsy. This study investigated the management practices involving learners with epilepsy in one selected school. The objectives of the study were to examine the existing practices in the management of epilepsy among learners in one selected regular school and to establish the challenges teachers face in the management of epilepsy in school. A qualitative case study design was used. The sample comprised 32 participants; 7 teachers, 5 parents, 5 learners with epilepsy and 15 learners without epilepsy. Data were collected through interviews and focus group discussions. Participants were selected through use of purposive sampling technique. Analysis of data was done thematically. The study revealed that the most common management practice used by most participants was making sure that learners with epilepsy adhered to medication prescribed by doctors; and making sure that learners with epilepsy are placed in a safe positions during seizure attacks. Among other findings, parents felt they were not fully educated on how to manage the children when under attack. Further, beliefs and myths about epilepsy still had a toll on the provision of services to learners with epilepsy. The study recommends that there should be a deliberate policy to orient and train stakeholders on the management of learners with epilepsy in schools and local communities. Efforts should be made to provide basic materials and equipment to use in the management of epileptic conditions in study schools. Schools, nearby clinics and hospitals build collaboration on the management of learners with epilepsy in institutions of learning.